Social Studies Learning in The Life of The City of Tomb of The Kings With a Structural Functionalism Perspective - Leli Anggreini Ningrum; Ayu Nurhania; Nur Jannah; Dock Chanthoeurn (Universitas Negeri Surabaya, 2023)
Learning Social Sciences is a multidisciplinary knowledge where one object of discussion can be seen from many social science perspectives. Observation in outdoor learning activities functions as a way to bring real situations to students. Indirectly as a real example of the social sciences being studied, applying essentialism which